REAKTIVASI ARANG AKTIF DARI LIMBAH DEPOT AIR MINUM ISI ULANG DI PONTIANAK KALIMANTAN BARAT Reactivation of Activated Carbon From Waste Depot Refill Drinking Water in Pontianak West Kalimantan - han, Jo; Wardenaar, Evi; Dirhamsyah, M. (Universitas Tanjungpura, 2015)
The study aims to determine the effective chemicals to produce activated charcoal waste which meets the Indonesian National Standard ISO - 06-3730-1995. The method used in this research is completely randomized design (CRD) with one factor, which consists of 4 treatments with 3 replicates. The treatment used in this study are chemicals consisting of 1% NaOH, KOH 25%, H3PO4 10% and 36% HCL. The results showed that the value of the physical characteristics of the waste activated carbon for water content ranged between 11-18%, the value of the chemical characteristics of the waste activated charcoal for substance evaporates levels ranged from 16.82 to 25.98%, ash content values ranged from 1.25 to 3.45%, and the value of bound carbon content ranging from 71.7 to 81.75%. Value characteristic absorption of iodine ranged from 1186.9 to 1211.9 mg / g. The results showed that the chemical treatment did not significantly affect the value of water content, levels of substance evaporates, bound carbon content and absorption of iodine and very significant effect on the value of ash. The mean scores for the test analysis of the characteristics of waste activated charcoal produced to meet the standard ISO - 06-3730-1995. The results showed that chemicals with activator H3PO4 obtain quality best waste activated charcoal. Keyword: Active charcoal, reactivation, waste water depot